Answer:
There are five triangles in a heptagon. A heptagon is a seven-sided polygon.
Step-by-step explanation:
Answer:
4. Parallelogram
5. Parallelogram
6. Parallelogram
Step-by-step explanation:
- 4. This is a parallelogram because the longer sides are parallel to each other and the shorter sides are also parallel to each other. Hence, this is a parallelogram.
- 5. This is a parallelogram because it's angles are the same to the opposite angles. Hence, this is a parallelogram.
- 6. This is a parallelogram because the longer sides are parallel to each other and the shorter sides are also parallel to each other. Hence, this is a parallelogram.
Hoped this helped.
Step-by-step explanation:
the introduction of a fraction tells us that we are dealing with multiplications, and therefore a geometric sequence (where every new term is created by multiplying the previous term by a constant factor, the ratio r).
I think your teacher made a mistake, or you made one when typing the question in here.
there is no factor r that creates
15×r = 9
and
9×r = 5/27
it would mean that
15 × r² = 5/27
r² = 5/27 / 15 = 5/27 × 1/15 = 5/405 = 1/81
r = 1/9
but 15 × 1/9 = 5 × 1/3 = 5/3 is NOT 9
and 9 × 1/9 = 9/9 = 1 is NOT 5/27
so, this can't be right.
on the other hand
15 × r = 9
r = 9/15 = 3/5
and then
9 × 3/5 = 27/5
so, either the sequence should have been
15, 5/3, 5/27
or (and I suspect this to be true)
15, 9, 27/5
under that assumption we have
s1 = 15
r = 3/5
sn = sn-1 × r = s1 × r^(n-1) = 15 × (3/5)^(n-1)
s10 = 15 × (3/5)⁹ = 15 × 19683/1953125 =
= 3 × 19683/390625 = 59049/390625 =
= 0.15116544 ≈ 0.151
Answer:
C
Step-by-step explanation:
The equation of a parabola in vertex form is
y = a(x - h)² + k
where (h, k) are the coordinates of the vertex and a is a multiplier
Given
y = 2x² + 12x + 1
To express in vertex form use the method of completing the square.
The coefficient of the x² term must be 1 , thus factor out 2 from 2x² + 12x
y = 2(x² + 6x) + 1
add/ subtract ( half the coefficient of the x- term)² to x² + 6x
y = 2(x² + 2(3)x + 9 - 9) + 1
= 2(x + 3)² - 18 + 1
= 2(x + 3)² - 17 → C